Динаміка зміни рівня забруднення атмосфери м. Одеса - Котельнікова, Ю.О.; Чугай, А.В. (Культура народов Причерноморья, 2014)
Одним з регіонів півдня України, що зазнає значного антропогенного впливу на атмосферне повітря, є Одеська область і, в першу чергу, м. Одеса. Одеса є рекреаційно-оздоровчим центром, у зв’язку з чим висуваються більш суворі вимоги до якості природних середовищ, в тому числі і атмосферного повітря. У роботі представлені результати оцінки якості атмосферного повітря на основі розрахунку індексу забруднення атмосфери та комплексного індексу забруднення атмосфери міста Одеса. Для оцінки використані дані багаторічних спостережень на мережі стаціонарних пості міста за 1995 – 2009 рр. за основними та деякими специфічними забруднюючими речовинами. Одним из регионов юга Украины, который подвергается значительному антропогенному воздействию на атмосферный воздух, является Одесская область и, в первую очередь, г. Одесса. Одесса является рекреационно-оздоровительным центром, в связи с чем выдвигаются более жесткие требования к качеству природных сред, в том числе и атмосферного воздуха. В работе представлены результаты оценки качества атмосферного воздуха на основе расчета индекса загрязнения атмосферы и комплексного индекса загрязнения атмосферы города Одесса. Для оценки использованы данные многолетних наблюдений на сети стационарных посте города за 1995 – 2009 гг. по основным и некоторыми специфическими загрязняющим веществам. Regions of Ukraine, including the South, characterized by significant anthropogenic impact on the air basin: in some of them major role are played industry, and in the others – increasing every year park of the car transport. Also, south Ukraine is the center of recreation and health, in connection with what are nominated more stringent requirements for quality of the natural environments, including for the atmospheric air. It should be noted that, nowadays, for analysis of the quality and condition of the atmospheric air used many indicators and methods. Ones allow to execute air basin quality assessment by the certain admixtures, other give an integrated assessment and analysis of atmospheric air in the region that is investigated. One of the south regions of Ukraine, which is undergoing significant anthropogenic impact on the atmospheric air, is the Odessa region and, especially, Odessa. Odessa is center of recreation and health, in connection with what are nominated more stringent requirements for quality of the natural environments, including for the atmospheric air. This work presents the results of the assessment of air quality based on the calculation the index of atmospheric pollution and the complex pollution index of the atmosphere of the city Odessa. To evaluate were used the long–term observations on the network of stationary posts of city with 1995 – 2009 for the basic and some specific pollutants. Obtained, that the index of atmospheric pollution for various pollutants generally exceeds sanitary and hygienic standards. The maximum value observed for substances such as dust, nitrogen dioxide, phenol and formaldehyde.